10. ANXIETY STATUS AMONG PRE-OPERATIVE PATIENTS UNDERGOING EMERGENCY SURGERIES AT THE EMERGENCY DEPARTMENT, THIEN HANH GENERAL HOSPITAL AND SOME RELATED FACTORS (Vietnam Journal of Community Medicine, 2025)
Objectives: To describe preoperative anxiety and identify some associated factors among emergency surgery patients at the Emergency Department of Thien Hanh General HospitalMethods: A cross-sectional study was conducted on 420 patients, who were directly interviewed using a structured questionnaire. Anxiety level was assessed using the Hospital Anxiety and Depression Scale – Anxiety (HADS-A). Data were analyzed using SPSS version 20.0. The Chi-square test was used to determine the differences in preoperative anxiety levels in relation to various variables.Results: The findings revealed a high prevalence of preoperative anxiety (82.4%). Specifically, mild anxiety accounted for 38.6%, moderate anxiety 20.7%, and severe anxiety 23.1%. The issue causing the most anxiety among patients was postoperative pain (51.9%). Statistically significant factors associated with preoperative anxiety included gender, history of chronic illness, history of previous surgeries, and type of current surgery (p
Keywords: Preoperative anxiety; Emergency surgery; Patients.